A nitrogen-doped carbon nanotube encapsulated nickel nanoparticle skeleton and its preparation and application

By designing a nitrogen-doped carbon nanotube encapsulated nickel nanoparticle framework on the negative electrode of sodium metal batteries, the problems of sodium deposition instability and dendrite growth are solved, and higher cycling performance and safety are achieved.

CN115939394BActive Publication Date: 2025-03-04ENERGY RES INST OF SHANDONG ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211558008.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-06
Publication Date
2025-03-04
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

Sodium deposition is unstable during the circulation process of sodium metal batteries, resulting in sodium dendrites growth, reducing Coulomb efficiency and cycle stability, and posing safety risks.

Method used

A nitrogen-doped carbon nanotube encapsulated nickel nanoparticle framework is designed to inhibit the growth of sodium dendrites and promote uniform deposition of sodium by introducing sodium philtically on the deposition framework and increasing the surface charge density.

Benefits of technology

Effectively inhibit the growth of sodium dendrites, improve the reversibility of electrodeposition and peeling of sodium metal negative electrodes, improve the cycle performance and Coulomb efficiency of the battery, and reduce safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115939394B_ABST
    Figure CN115939394B_ABST
Patent Text Reader

Abstract

The present invention provides a nitrogen-doped carbon nanotube encapsulated nickel nanoparticle skeleton and its preparation and application, thereby inhibiting the growth of sodium dendrites, improving the reversibility of sodium metal negative electrode electrodeposition and stripping, and achieving high coulombic efficiency and stable cycle of metallic sodium in half-cell and symmetric cell tests. The deposited skeleton of the present invention has a large specific surface area, can effectively reduce the local current density, inhibit the growth of sodium dendrites, and alleviate volume expansion; nitrogen doping increases the sodium affinity of the deposited skeleton, can reduce the nucleation overpotential, and has a strong local electron density, which can induce uniform deposition of sodium; in addition, free electrons can be transferred from nickel nanoparticles to the carbon layer, so that the carbon surface is enriched with electrons, and promotes the uniform deposition of sodium on the skeleton surface. The deposited skeleton of the present invention can improve the cycle performance of the battery and will provide a new idea for the development of a stable sodium metal negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage batteries, and in particular to a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, rechargeable battery technology has rapidly penetrated into many consumer products and industrial systems. It has become an urgent need to develop rechargeable batteries with their own unique advantages. Traditional lithium-ion batteries have almost reached their theoretical energy density limit. The natural scarcity of lithium reserves has seriously restricted the large-scale application of lithium-ion batteries, and it is necessary to explore alternative batteries. Sodium metal batteries have a high theoretical capacity (1165 mA·h·g) because sodium is widely distributed in the earth's crust and has abundant reserves. -1 ) and a lower electrochemical potential (-2.71 V vs. standard hydrogen electrode), it has become a promising candidate for high energy density batteries. However, the practical application of sodium metal anodes is hampered by the growth of sodium dendrites, which lead to low coulombic efficiency and poor cycling stability of sodium metal anodes. Excessive dendrite growth can even pierce the separator, causing battery short circuit and causing serious safety issues.

[0004] Therefore, how to stabilize the deposition and stripping of sodium and inhibit the growth of sodium dendrites during the battery cycle is the key to promoting the development of sodium metal batteries, but it also poses great challenges.

[0005] Changing the electrolyte formula, such as using ether-based electrolyte, high-concentration electrolyte or a small amount of additives, can adjust the reaction activity of metallic sodium with the electrolyte and improve the stability of the SEI film; constructing an artificial SEI film with good mechanical strength and ionic conductivity can protect metallic sodium from corrosion by the electrolyte. However, the SEI film formed in this way cannot withstand the mechanical deformation caused by dendrite growth. In addition, the artificially constructed SEI film will reduce the interfacial resistance and hinder the migration of Na ions. In contrast, designing a deposition skeleton for the "host-free" sodium metal anode can effectively reduce the local current density, inhibit the formation of sodium dendrites, alleviate volume expansion, and reduce meaningless electrolyte consumption. Among them, modifying the "sodium-philic" functional groups (nitrogen doping, etc.) on the deposition skeleton can increase the binding energy between sodium and the deposition skeleton, reduce the nucleation overpotential of sodium and induce uniform deposition of sodium. In addition, since the doped atoms participate in the delocalized π system of carbon, they have a strong local electron density and high electronegativity, which further promotes the adsorption of sodium on the surface of the deposition skeleton.

[0006] It can be seen that introducing "sodium-philic" sites into the sodium deposition skeleton and increasing its surface charge density can induce uniform deposition of sodium and effectively improve the reversible electroplating / stripping properties of the sodium metal anode. Summary of the invention

[0007] In order to solve the deficiencies of the prior art, the present invention provides a nitrogen-doped carbon nanotube encapsulated nickel nanoparticle skeleton and its preparation and application, the purpose of which is to inhibit the growth of sodium dendrites and improve the reversibility of sodium metal negative electrode electrodeposition and stripping.

[0008] In order to achieve the above object, the technical solution of the present invention is:

[0009] The first aspect of the present invention provides a method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton, characterized in that the specific steps are:

[0010] Step 1: dissolving dimethylglyoxime and polyethylene glycol 2000 in anhydrous ethanol to obtain solution A; dissolving nickel chloride hexahydrate in deionized water to obtain solution B;

[0011] Among them, the mass of dimethylglyoxime is 1-1.5 g, the mass of polyethylene glycol 2000 is 6-12 g, the amount of anhydrous ethanol is 80-120 ml; the mass of nickel chloride hexahydrate is 2-3 g, and the amount of deionized water is 80-120 ml;

[0012] Step 2: Refrigerate solution A and solution B in a refrigerator, then quickly pour solution A into solution B, let it stand for a few hours, and then filter;

[0013] Step 3: drying the above product and placing it in a tube furnace, adding melamine for calcination to obtain the nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0014] The second aspect of the present invention provides a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton, which is prepared according to the above-mentioned preparation method.

[0015] The third aspect of the present invention provides the use of the above-mentioned nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton in energy storage batteries.

[0016] The beneficial effects of the present invention are:

[0017] (1) The present invention prepares a nitrogen-doped carbon nanofiber with a bamboo-like structure, specifically, bamboo-like nitrogen-doped carbon nanotubes are grown on carbon fibers, which increases the specific surface area of ​​the material, effectively reduces the local current density, inhibits the growth of sodium dendrites, and alleviates volume expansion. Nitrogen doping increases the sodium affinity of the deposition skeleton, can reduce the nucleation overpotential, and has a strong local electron density, inducing uniform deposition of sodium. In addition, free electrons can be transferred from nickel nanoparticles to the carbon layer, enriching the carbon surface with electrons and promoting uniform deposition of sodium on the skeleton surface.

[0018] (2) The present invention designs a sodium metal negative electrode deposition skeleton encapsulated with nickel nanoparticles in nitrogen-doped carbon nanotubes to inhibit the growth of sodium dendrites and improve the reversibility of electrodeposition and stripping of the sodium metal negative electrode. This effectively improves the cycle performance of the battery and will provide new ideas for the development of a stable sodium metal negative electrode.

[0019] (3) The present invention constructs a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle sodium deposition framework, which can achieve high coulombic efficiency and stable cycle of metallic sodium in half-cell and symmetric cell tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 This is a scanning electron microscope photo of the sample prepared in Example 1;

[0022] Figure 2 This is a transmission electron microscope photo of the sample prepared in Example 1;

[0023] Figure 3 The half-cell assembled from the sample prepared in Example 1 was -2 The current density,

[0024] 1 mA·h·cm -2 Coulombic efficiency at area capacity;

[0025] Figure 4 The half-cell assembled from the sample prepared in Example 1 was -2 The current density,

[0026] 1 mA·h·cm -2 Plating / stripping voltage curve under area capacity;

[0027] Figure 5 The symmetrical battery assembled from the samples prepared in Example 1 and Comparative Example 1 has a -2Current density, 1 mA·h·cm -2 Cycling performance at area capacity. DETAILED DESCRIPTION

[0028] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0029] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0030] The present invention relates to a nitrogen-doped carbon nanotube encapsulated nickel nanoparticle skeleton and its preparation and application. The purpose of the present invention is to provide a method for improving the reversibility of electrodeposition and stripping of a sodium metal negative electrode. Specifically, the following scheme is adopted:

[0031] Dissolve dimethylglyoxime and polyethylene glycol 2000 in anhydrous ethanol to obtain solution A, dissolve nickel chloride hexahydrate in deionized water to obtain solution B, refrigerate the two solutions in a refrigerator, then quickly pour solution A into solution B or quickly pour solution B into solution A, let stand for several hours and then filter, dry the product and place it in a tube furnace, add melamine and calcine to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0032] After the reaction is completed, a nitrogen-doped carbon nanofiber with a bamboo-like structure is obtained, which increases the specific surface area of ​​the material, effectively reduces the local current density, and inhibits the growth of sodium dendrites. Nitrogen doping increases the sodium affinity of the deposition skeleton, which can reduce the nucleation overpotential and induce uniform deposition of sodium. In addition, free electrons can be transferred from nickel nanoparticles to the carbon layer, so that the carbon surface is enriched with electrons and promotes the uniform deposition of sodium on the skeleton surface. The present invention effectively improves the cycle performance of the battery by designing a nitrogen-doped carbon nanotube encapsulated nickel nanoparticle sodium metal negative electrode deposition skeleton, which will provide new ideas for the development of a stable sodium metal negative electrode.

[0033] In a typical embodiment of the present invention, a method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton is provided, and the specific steps are as follows:

[0034] Step 1: dissolving dimethylglyoxime and polyethylene glycol 2000 in anhydrous ethanol to obtain solution A; dissolving nickel chloride hexahydrate in deionized water to obtain solution B;

[0035] Among them, the mass of dimethylglyoxime is 1-1.5 g, the mass of polyethylene glycol 2000 is 6-12 g, the amount of anhydrous ethanol is 80-120 ml; the mass of nickel chloride hexahydrate is 2-3 g, and the amount of deionized water is 80-120 ml;

[0036] Step 2: Place solution A and solution B in a refrigerator, then quickly pour solution A into solution B or quickly pour solution B into solution A, let stand for a few hours and then filter;

[0037] Step 3: drying the above product and placing it in a tube furnace, adding melamine for calcination to obtain the nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0038] In some examples of this embodiment, in the step 1, the mass of diacetyl oxime is 1.2 g, the mass of polyethylene glycol 2000 is 10 g, and the amount of anhydrous ethanol is 100 ml.

[0039] In some examples of this embodiment, in the step 1, the mass of nickel chloride hexahydrate is 2.4 g; and the amount of deionized water used is 100 ml.

[0040] In some examples of this embodiment, in step 2, solution A and solution B are refrigerated in a refrigerator for 1 to 3 hours at a refrigeration temperature of 2 to 6°C;

[0041] Preferably, the refrigeration time is 2 h;

[0042] Preferably, the refrigeration temperature is 4°C.

[0043] In some examples of this embodiment, in the step 2, when pouring solution A into solution B, a magnetic particle is added and stirred continuously at a speed of 600-800 r / min, and stirring is stopped after pouring, and the mixture is allowed to stand for 3-5 h;

[0044] Preferably, the rotation speed is 800 r / min;

[0045] Preferably, the standing time is 5 h.

[0046] In some examples of this embodiment, in step 3, the drying temperature of the product is 60° C., the drying time is 6 to 10 h to obtain a precursor, the mass of the calcined melamine is 5 to 8 times the mass of the precursor, and the melamine is placed 2.5 to 3.5 cm upstream of the precursor;

[0047] Preferably, the drying time is 8 h.

[0048] In some examples of this embodiment, in step 3, the mass of the calcined melamine is 5 to 8 times the mass of the precursor, and the melamine is placed 2.5 to 3.5 cm upstream of the precursor;

[0049] Preferably, the mass of the calcined melamine is 7 to 8 times the mass of the precursor;

[0050] Preferably, the melamine is placed 3 cm upstream of the precursor.

[0051] In some examples of this embodiment, in step 3, the calcination atmosphere is argon, the calcination temperature is 500-700°C, the time is 1-3 h, and the heating rate is 2-8°C / min;

[0052] Preferably, the calcination temperature is 600°C;

[0053] Preferably, the calcination time is 2 h;

[0054] Preferably, the heating rate is 2°C / min.

[0055] In another typical embodiment of the present invention, a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton is provided, which is prepared according to the above-mentioned preparation method.

[0056] In another typical embodiment of the present invention, there is provided application of the above-mentioned nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton in energy storage batteries.

[0057] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0058] Example 1

[0059] Step (1): Dissolve 1.2 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0060] Step (2): Dissolve 2.4 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0061] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 2 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0062] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tube furnace for calcination, wherein the mass of melamine is 7 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor. The precursor is calcined at 600°C for 2 h under nitrogen at a heating rate of 2°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0063] Figure 1 This is a scanning electron microscope photo of the sample prepared in Example 1; Figure 2 This is a transmission electron microscope photo of the sample prepared in Example 1; Figure 3 The half-cell assembled from the sample prepared in Example 1 was -2 Current density, 1mA·h·cm -2 Coulombic efficiency at area capacity; Figure 4 The half-cell assembled from the sample prepared in Example 1 was -2 Current density, 1 mA·h·cm -2 The plating / stripping voltage curve under the area capacity; from Figure 4 It can be seen that with the increase in the number of cycles, the sodium plating / stripping voltage curves almost overlap, and the overpotential remains unchanged, indicating that the half-cell assembled with the sample prepared in Example 1 has good cycle stability, and the sample can effectively inhibit the growth of sodium dendrites and improve the reversibility of sodium metal negative electrode electrodeposition and stripping.

[0064] Example 2

[0065] Step (1): Dissolve 1.5 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0066] Step (2): Dissolve 2.4 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0067] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 2 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0068] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tube furnace for calcination, wherein the mass of melamine is 7 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor. The precursor is calcined at 600°C for 2 h under nitrogen at a heating rate of 2°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0069] Example 3

[0070] Step (1): Dissolve 1.2 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0071] Step (2): Dissolve 2.4 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0072] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 2 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0073] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tubular furnace for calcination, wherein the mass of melamine is 8 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor. The precursor is calcined at 500°C for 2 h under nitrogen at a heating rate of 2°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0074] Example 4

[0075] Step (1): Dissolve 1.2 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0076] Step (2): Dissolve 2.4 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0077] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 2 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0078] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tube furnace for calcination, wherein the mass of melamine is 7 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor. The precursor is calcined at 500°C for 2 h under nitrogen at a heating rate of 5°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0079] Example 5

[0080] Step (1): Dissolve 1.2 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0081] Step (2): Dissolve 3.0 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0082] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 3 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0083] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tube furnace for calcination, wherein the mass of melamine is 7 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor. The precursor is calcined at 600°C for 2 h under nitrogen at a heating rate of 2°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0084] Comparative Example 1

[0085] Step (1): Dissolve 1.5 g of dimethylglyoxime and 6 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0086] Step (2): Dissolve 2.0 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0087] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 1 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0088] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tubular furnace for calcination, wherein the mass of melamine is 7 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor, and calcining at 600°C for 2 h under nitrogen at a heating rate of 5°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0089] Figure 5 The symmetrical battery assembled from the samples prepared in Example 1 and Comparative Example 1 has a -2 Current density, 1 mA·h·cm -2 The cycling performance under the area capacity. It can be seen that as the cycle progresses, the symmetrical battery assembled from the sample prepared in Comparative Example 1 has significant random voltage fluctuations, indicating serious side reactions and dendrite formation. The symmetrical battery assembled from the sample prepared in Example 1 can be stably cycled for more than 1400h, indicating that it has the unique advantages of uniform nucleation and stable sodium plating / stripping.

[0090] Comparative Example 2

[0091] Step (1): Dissolve 1.2 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0092] Step (2): Dissolve 2.4 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0093] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 2 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0094] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tubular furnace for calcination, wherein the mass of melamine is 8 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor, and calcining at 500°C for 2 h under nitrogen at a heating rate of 5°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0095] Comparative Example 3

[0096] Step (1): Dissolve 1.2 g of dimethylglyoxime and 10 g of polyethylene glycol 2000 in 100 ml of anhydrous ethanol (solution A).

[0097] Step (2): Dissolve 3.0 g of nickel chloride hexahydrate in 100 ml of deionized water (Solution B).

[0098] Step (3): Place solution A and solution B in a refrigerator and refrigerate at 4 °C for 3 h. Then quickly pour solution A into solution B and add a magnetic bar to stir continuously at a speed of 800 r / min. Stop stirring after pouring. Let it stand for 5 h and then filter.

[0099] Step (4): drying the above product in a forced air drying oven at 60°C for 8 h to obtain a precursor, placing the precursor and melamine in a tubular furnace for calcination, wherein the mass of melamine is 7 times that of the precursor, and melamine is placed about 3 cm upstream of the precursor. The precursor is calcined at 700°C for 1 h under nitrogen at a heating rate of 2°C / min to obtain a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton.

[0100] The samples prepared in Examples 1, 2, 3 and Comparative Example 1 were mixed with sodium alginate in a mass ratio of 8:1, ground into slurry with deionized water, and then evenly coated on copper foil with a scraper, placed in an oven at 60 ° C for vacuum drying for 12 hours, and then made into a disc with a diameter of 1.2 cm using a punching machine, and used as the positive electrode, the counter electrode was a metal sodium sheet, and assembled into a half-cell in a glove box; and pre-electroplated with 8 mA·h·cm-2 of sodium on the sample, disassembled and taken out the pre-electroplated sodium sample, and assembled into a symmetrical battery as the positive and negative electrodes. Among them, the electrolyte is 1 M sodium hexafluorophosphate dissolved in diethylene glycol dimethyl ether, and the diaphragm is glass microfiber Whatman GF / F. Battery performance tests were carried out at different current densities and area capacities.

[0101] The test results of the half-cells and symmetrical cells prepared in Examples 1, 2, 3 and Comparative Example 1 of the present invention under different current density and area capacity test conditions are shown in Table 1:

[0102] Table 1

[0103]

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton, characterized in that: The specific steps are: Step 1: dissolving dimethylglyoxime and polyethylene glycol 2000 in anhydrous ethanol to obtain solution A; dissolving nickel chloride hexahydrate in deionized water to obtain solution B; Among them, the mass of dimethylglyoxime is 1-1.5 g, the mass of polyethylene glycol 2000 is 6-12 g, the amount of anhydrous ethanol is 80-120 ml; the mass of nickel chloride hexahydrate is 2-3 g, and the amount of deionized water is 80-120 ml; Step 2: Refrigerate solution A and solution B in a refrigerator, then quickly pour solution A into solution B or quickly pour solution B into solution A, let stand for a few hours and then filter; Step 3: drying the product obtained in step 2, placing it in a tube furnace, and adding melamine for calcination to obtain the nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton; The product was dried at 60 °C and for 6 to 10 h to obtain the precursor; The mass of the calcined melamine is 5 to 8 times the mass of the precursor, and the melamine is placed 2.5 to 3.5 cm upstream of the precursor; The calcination atmosphere is argon, the calcination temperature is 500~700 ℃, the time is 1~3 h, and the heating rate is 2~8 ℃ / min.

2. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 1, the mass of dimethylglyoxime is 1.2 g, the mass of polyethylene glycol 2000 is 10 g, and the amount of anhydrous ethanol is 100 ml.

3. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 1, the mass of nickel chloride hexahydrate is 2.4 g; the amount of deionized water used is 100 ml.

4. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 2, solution A and solution B are refrigerated in the refrigerator for 1 to 3 hours at a temperature of 2 to 6°C.

5. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 2, the refrigeration time is 2 h; the refrigeration temperature is 4 °C.

6. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 2, when pouring solution A into solution B, a magnetic bar is added and stirred continuously at a speed of 600-800 r / min. After pouring, stirring is stopped and the mixture is allowed to stand for 3-5 hours.

7. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 2, when solution A is poured into solution B, a magnetic stirrer is added and the rotation speed is 800 r / min; the standing time is 5 h.

8. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step 3, the drying time is 8 h to obtain the precursor.

9. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step three, the mass of the calcined melamine is 7 to 8 times the mass of the precursor; and the melamine is placed 3 cm upstream of the precursor.

10. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step three, the calcination atmosphere is argon, the calcination temperature is 500-700°C, the time is 1-3 h, and the heating rate is 2-8°C / min.

11. The method for preparing a nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 1, characterized in that: In the step three, the calcination temperature is 600°C; the calcination time is 2 h; and the heating rate is 2°C / min.

12. A nitrogen-doped carbon nanotube encapsulated nickel nanoparticle skeleton, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 11.

13. Use of the nitrogen-doped carbon nanotube-encapsulated nickel nanoparticle skeleton as claimed in claim 12 in energy storage batteries.

Citation Information

Patent Citations

  • Preparation method for hollow porous carbon composite material

    CN105776130A